Research Progress in Classical Swine Fever Virus Detection and Classical Swine Fever Vaccines - Pu ZHANG; Jiankai CHEN; Yuehui LAI; Derui LIN; Fukun LI; Xiaomin ZHOU; Gaowei HOU; Dongmei QI (Guangdong nongye kexue, 2022)
Classical Swine Fever (CSF) is a highly infectious and fatal disease caused by Classical Swine Fever Virus (CSFV). It is recognized as one of the most serious viral diseases in pig industry. Since CSF was first reported in 1810, CSF has caused significant economic losses to the pig industry in the world and continues to threaten global pork production and human food security. CSF was listed as one of the most important notifiable infectious diseases by the World Organization for Animal Health (OIE), and it was listed as "Class I infectious diseases" in China. At present, CSF is clinically manifested complicated and changeably as acute form with high mortality or subacute type, chronic type, recessive type and continuous infection type with variable mortality, and often infected combined with various diseases. Vaccination is still one of the main means to prevent and control CSF in most countries, especially in developing countries. The development and application of various laboratory diagnostic methods and clinical detection techniques for CSFV antigens and antibodies play a very important role in the prevention and control of CSF. With the rapid development of biotechnology, more diagnostic techniques and new-type vaccines for CSFV have been developed and approved. CSFV antigen and antibody diagnostic techniques, and the development and prospects of live attenuated and new-type CSFV vaccines such as subunit and vector vaccines are reviewed in order to provide references for better prevention and control of CSF.